STUDENTS’ PERFORMANCE IN LEARNING AIR CONDITIONING BUILDING SYSTEM THROUGH EXPERIENCE BASED LEARNING METHOD - Herda Balqis Ismail; Siti Shahidah Sharipudin; Maisarah Noorezam; Azinoor Azida Abu Bakar; Asmawati Che Hasan; Nurjuhanah Juhari; Siti Saffura Sharipudin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Building services are integral to civil engineering, contributing to functionality, sustainability, and efficiency. The Building Services course (ECM346) in the Civil Engineering Diploma Program (CEEC110) at UiTM involves theoretical and practical components, emphasizing electrical and mechanical system in buildings. Heating, Ventilating and Air Conditioning (HVAC) systems, a crucial aspect of building services, are examined in detail, given their importance in maintaining optimal indoor environments. However, teaching these services to diploma-level civil engineering students is challenging because of the technical and dynamic character of the subject. This study aims to compare the performance of two groups from different semesters using two teaching methods: conventional teaching and experience-based learning with a site visit. The research explores the impact of these methods on students’ understanding of Air Conditioning Systems (ACS), considering factors such as gender and site visit experience. Data collection involves information on student participation, demographics, and performance in the summative assessment, focusing on air conditioning system-related questions. Statistical analysis, including t-tests and box plot analysis, is employed to compare the two groups of students based on teaching methods and gender. The students with a site visit experience perform significantly better in understanding ACS compared to those without. The box plot analysis illustrates the higher median and better distribution of scores for students with a site visit. A gender-based analysis indicates no significant difference in understanding between male and female students with a site visit. In contrast, a significant difference exists in the group without a site visit. The study recommends integrating more experiential learning in civil engineering education to enhance practical understanding and prepare students for industry challenges. This research contributes to the pedagogical understanding of effective teaching methods in civil engineering education, emphasizing the importance of practical experiences, such as site visits, in enhancing students’ comprehension of complex topics.